2014
DOI: 10.1186/1750-0680-9-2
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying and understanding carbon storage and sequestration within the Eastern Arc Mountains of Tanzania, a tropical biodiversity hotspot

Abstract: BackgroundThe carbon stored in vegetation varies across tropical landscapes due to a complex mix of climatic and edaphic variables, as well as direct human interventions such as deforestation and forest degradation. Mapping and monitoring this variation is essential if policy developments such as REDD+ (Reducing Emissions from Deforestation and Forest Degradation) are to be known to have succeeded or failed.ResultsWe produce a map of carbon storage across the watershed of the Tanzanian Eastern Arc Mountains (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 87 publications
1
21
1
3
Order By: Relevance
“…Applying the carbon values to the modern day (2000) land cover map results in landscape‐scale carbon estimates similar to comparable regional estimates presented elsewhere in the literature (Willcock et al ., , ), but larger than most globally derived estimates [Baccini et al . (, ), Saatchi et al .…”
Section: Discussionmentioning
confidence: 75%
“…Applying the carbon values to the modern day (2000) land cover map results in landscape‐scale carbon estimates similar to comparable regional estimates presented elsewhere in the literature (Willcock et al ., , ), but larger than most globally derived estimates [Baccini et al . (, ), Saatchi et al .…”
Section: Discussionmentioning
confidence: 75%
“…The author concluded that avoided forest degradation at the study sites would have increased standing woody biomass up to 4.0 t ha -1 year -1 over the 22-year period. Recently, [45] found that carbon storage in the tree-dominated ecosystems of the Tanzanian Eastern Arc Mountains has decreased at a mean rate of 1.47 Mg C ha -1 yr -1 (ca. 2% of the stocks of carbon per year) due to 74% forest area loss driven by 5-fold increase in cropland area.…”
Section: Biomass and Carbon Dynamicsmentioning
confidence: 99%
“…Woody biomass was observed to range from 1.5 Mg ha -1 (3-6 years old coppice) to 144 Mg ha -1 (mature wet Miombo) [9,[41][42][43][44][45]. Dry Miombo ranges between 53-55 Mg ha -1 [45][46][47][48]. It is confirmed that wood and soil compartments are the most important of these stocks [48][49], but grass, litter and root may contribute significantly to carbon sequestration.…”
Section: Biomass and Carbon Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is recognised that there are relatively few studies from the direct study area, or even from Malawi as a whole. Future studies could use weighted means, giving more influence to values geographically nearer to the study area (Willcock et al, 2014;Willcock et al, 2012).…”
Section: Study Limitationsmentioning
confidence: 99%